A design strategy for achieving more than 90% of the overlap integral of electron and hole wavefunctions in high-AlN-mole-fraction AlxGa1−xN multiple quantum wells. (21st December 2016) - Kojima, Kazunobu; Furusawa, Kentaro; Yamazaki, Yoshiki; Miyake, Hideto; Hiramatsu, Kazumasa; Chichibu, Shigefusa F.
Abstract: A strategy for increasing the square of an overlap integral of electron and hole wavefunctions ( I 2 ) in polar c -plane Al x Ga1− x N multiple quantum wells (MQWs) is proposed. By applying quadratic modulation to AlN mole fractions along the c -axis, local bandgap energies and concentrations of immobile charges induced by polarization discontinuity are simultaneously controlled throughout the MQW structure, and optimized band profiles are eventually achieved. The I 2 value can be substantially increased to 94% when the well width ( L w ) is smaller than 4.0 nm. In addition, I 2 greater than 80% is predicted even for thick MQWs with L w of 10 nm.